Supply Chain Performance Measurement Model at PT. Metito Indonesia Based On Business Intelligence Power BI - Banggas Hanistia Pahlavi; Imam Djati Widodo (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
Supply chain is one of the important aspects in a company. An effective supply chain can help companies to increase efficiency, effectiveness, and profitability. The purpose of this research is to develop a supply chain performance measurement model at PT Metito Indonesia based on Power BI Business Intelligence. This research is a type of qualitative research that uses a descriptive approach. The data collection technique in this research was carried out by observation and literature study. This research was conducted at PT Metito Indonesia which is located at Jl. Ampera Raya No. 18A, East Cilandak, Kemang, South Jakarta. Data validity tests in this study include tests, credibility, transferability, dependability, and confirmability. The research results show that measuring supply chain performance at PT Metito Indonesia can increase its competitiveness by adopting strategies that are more adaptive and responsive to market changes. Using BI Power BI helps companies to be more proactive in making strategic decisions that have a direct impact on increasing competitiveness in the market, increasing operational efficiency, and strengthening the company's position in a competitive industry.